Peirce’s Sign Analysis On Djarum 76 Commercial Advertisement: (Semiotics) - Hidayati, Alfin Fuji; Finasyahadatina (Calakan : Jurnal Sastra, Bahasa, dan Budaya, 2025)
The purpose of this study is to find out the implicit meaning of the Djarum 76 advertisement on Youtube or television. Youtube or television is one of the media or tools to promote and persuade people or customers to be interested in the product. Media takes on an important role in communication to convey the implied meaning of advertising to customers. Meaning and advertising are inseparable from each other. Each ad contains a hidden message that must be interpreted. Cigarette advertising should be limited in persuading people. In creating an advertisement, advertisers are encouraged to be more creative in packaging the product advertisement. Cigarette advertising is prohibited from displaying products and product users. Cigarette ads should only feature images and images of the product. These ads are commercial in nature, which is why the author was interested in analyzing these ads. The method used in this study is a descriptive qualitative method used to describe the hidden messages in these ads.